Anthony Lake papers - Lake, Anthony
Correspondence, speeches, writings, articles, reports, notes, testimony, press interviews, travel files, campaign files, position papers, press releases, production records, reviews, appointment books, family papers, financial and legal records, copies of surveillance logs, clippings, and other papers documenting Lake's activities in the foreign service and as head of the National Security Council during President Bill Clinton's first term.
Documents Lake's foreign service in Vietnam (1962-1965), his lawsuit against Nixon administration officials for the FBI wiretapping of Lake's home in 1970 and 1971, his years as President Jimmy Carter's director of policy planning in the State Dept. (1977-1981), his tenure at Amherst College and at Mount Holyoke as Five College Professor in international relations (1981-1992), his work as senior foreign policy advisor for Clinton's 1992 presidential campaign, his role as national security advisor to President Clinton (1993-1997), and his work as the Clinton administation's special envoy in the border dispute between Ethiopia and Eritrea (1999) and in Haiti (1998-2000).
Correspondents and analysts include Les Aspin, C. Fred Bergsten, Richard C. Bush, Michael Clough, Stuart Eizenstat, Richard C. Holbrooke, Penn Kemble, Sol M. Linowitz, Richard Schifter, Gary Sick, Nancy Soderberg, and U.S. Dept. of Defense.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division, Recorded Sound Section.
Assistant to the president for national security affairs and foreign service officer. Full name: William Anthony Kirsopp Lake; born 1939.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aspin, Les; Bergsten, C. Fred, -- 1941-; Bush, Richard C., -- 1947-; Clinton, Bill, -- 1946-; Clough, Michael; Eizenstat, Stuart; Holbrooke, Richard C., -- 1941-2010.; Kemble, Penn; Linowitz, Sol M., -- 1913-2005.; Schifter, Richard; Sick, Gary, -- 1935-; Soderberg, Nancy E., -- 1958-; Lake family; United States. -- Department of Defense; United States. -- Department of State. -- Officials and employees; United States. -- Federal Bureau of Investigation; Amherst College -- Faculty; Mount Holyoke College -- Faculty; National Security Council (U.S.); Diplomatic and consular service, American; International relations; National security -- United States; Presidents -- United States -- Election -- 1992.; Vietnam War, 1961-1975 -- Diplomatic history; Wiretapping -- United States; Eritrea -- Boundaries -- Ethiopia; Ethiopia -- Boundaries -- Eritrea; Haiti -- Politics and government -- 1986-; United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- 1989-; United States -- Foreign relations -- Vietnam; Vietnam -- Foreign relations -- United States; Foreign service officers; Presidential advisors